STARTEGI PEMBERIAN KOMPENSASI DAN PENGENDALIAN INTERNAL TERHADAP KINERJA KARYAWAN - Husin; Safaruddin; Tuti Dharmawati; Ika Maya Sari (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2021)
This study aims to examine the effect of compensation and internal control on employee performance. This research was conducted at PT. Hasrat Abadi branch kendari. The sample in this research is as much as 20 responden by using sample saturation that is sample determination technique with all member of population used as sample. Methods of data collection is done by using questionnaires that have been distributed to all respondents. Technique analysis using multiple linear regression analysis method. The results of this study indicate that the compensation effect partially and significantly on employee performance, Internal controls influence partially but not significant to employee performance. Compensation and internal control simultaneously affect employee performance. This means the fairer the compensation and the better the company's internal control can improve employee performance.